The internationalization of high education at the State University of Western Paraná - UNIOESTE: from passivity to an institutional policy of internationalization - Bastos, Carmen Celia Barradas Correia; Manchope, Elenita Conegero Pastor; Assenza, Marta Lucia Alves (Universidade Estadual de Campinas, 2019)
Instituted as a University since 1994, the Western Paraná State University – UNIOESTE has sought to apply an internal policy of internationalization. One of its potentialities is to characterize itself as a multicampi University in a region of triple border formed by Brazil, Argentina and Paraguay while covering 94 municipalities in the western and southwestern regions of Paraná. Although having an International Relations Office in its organizational structure since its implementation, it was only in 2017 that an institutional policy of internationalization was regulated. During the previous twenty years, what happened in UNIOESTE were isolated actions of teachers in international activities or participations in mobility programs. The objective of this article is to present the institutional reality of our university in relation to the internationalization process in the last 22 years, from a passive internationalization condition to the beginning of a consolidation of its institutional policy. The presentation and discussion seek to consolidate the concept of internationalization that mediates the work and intentions of UNIOESTE in the scope of the policy of student mobility, teachers and employees as well as the path to reach an institutional policy of internationalization. In order to reach this objective, an analytical methodology of data on mobility, reading of bibliography about the subject and a qualification of the information, using the data collected and the concepts worked have been used. The result is a chain of historical facts and actions that culminated in the approval of the internal policy of internationalization.